(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Autoimmune rheumatic diseases represent a diverse and complex group of disorders in which the immune system mistakenly targets the body’s own tissues, resulting in chronic inflammation and tissue damage across multiple organ systems. These diseases, such as rheumatoid arthritis, systemic lupus erythematosus, and Sjögren’s syndrome, are characterized by their heterogeneous clinical manifestations, unpredictable course, and potential for significant morbidity. In the management of these disorders, early and accurate assessment of disease activity as well as timely monitoring of treatment response are critical. Among various tools used in clinical practice, inflammatory markers play a central role in both the diagnosis and ongoing evaluation of autoimmune rheumatic diseases.